Some more recent results concerning weak Asplund spaces - Warren B. Moors (Abstract and Applied Analysis)
In this paper, we will present some of the latest advances that have occurred in the study of weak Asplund spaces. In particular, we will give an example of a Gâteaux differentiability space that is not weak Asplund.